Psychological Dimensions of the Family in the Uleman Ago Nikahken Anak Tradition of the Lampung Pepadun: Perspectives of Marcel Mauss's Reciprocity and 'Urf - Annikmah Farida; Bustanul Arifin; Sri Sudono Saliro; Saipudin Saipudin; Etika Rini; Khairul Aripin (Bulletin of Counseling and Psychotherapy, 2025)
The traditional practice of Uleman in the Lampung Pepadun community is often only seen as an Uleman ritual, even though there is a reciprocity mechanism that has a profound impact on the psychological and economic dimensions of the family. This study aims to analyze the practice of Uleman ago nikahken children as a construction of moral obligations using the perspective of Reciprocity Marcel Mauss and the concept of 'Urf Islamic law. Through the qualitative method of field studies in Central Lampung, it was found that the Uleman is an instrument of social legitimacy with four symbolic levels: nagau, cloth, cigarettes, and cleaning tools. Psychologically, the high intensity of the Uleman creates chronic strain for the family in order to maintain dignity (Pi'il Pesenggiri). The inability to reciprocate giving is perceived as a social failure, thus triggering a coping strategy through collective support. Although financially burdensome, this tradition is categorized as 'Urf Saheeh because its essence strengthens solidarity (Sakai Sambayan) and friendship. This study concludes that the psychological dimension in Ulemans is born from the negotiation between moral responsibility, economic capacity, and efforts to maintain family honor under community supervision. The sustainability of this tradition depends on the balance between the preservation of honorary values and the principle of welfare so as not to become a structural burden on Muslim families.